The Empowerment of Underprivileged Families of Mr. Ahmad Suki - Rosa, Nurhaliza; Ariyanti, Pipit; Safitri, Nadia (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This program aims to empower underprivileged families in Pelangi Village, particularly Mr. Ahmad Suki’s family, by enhancing their knowledge and skills to achieve economic independence through entrepreneurship.Method: The program includes entrepreneurship training focused on motivation, business planning, record-keeping, and profit-loss analysis. Sales of food products like geprek chicken, risol, and basreng were used as part of the practical training. Interviews with Mr. Ahmad Suki’s family guided the program’s development.Practical Applications: The skills learned can be applied to small business ventures, helping underprivileged communities achieve financial independence through sustainable entrepreneurship.Conclusion: The program was successful due to continuous support and collaboration, empowering the community by equipping them with essential business skills for economic improvement.